Cardiac remodeling in the acute period of Q-myocardial infarction, complicated by acute heart failure and hyperglycemia - V. D. Syvolap; N. I. Kapshytar (Zaporozhye State Medical University, 2019)
The aim was to study structural, geometric and functional heart reconstruction in acute period of Q-myocardial infarction (Q-MI) complicated by acute heart failure (AHF) and hyperglycemia (HG). Materials and methods. The study included 139 patients in acute period of Q-MI complicated by AHF. On admission, HG was diagnosed in 108 patients: 23 cases of type 2 diabetes in history, 34 - stress HG, 26 - impaired glucose tolerance (IGT), 25 - first identified diabetes. The level of glycemia and glycemic profile (GP) were determined in patients, the standard deviation and the coefficient of GP variation were calculated, the heart structural, geometric and functional parameters were measured. Results. The increase by16 % in ESD and 29 % in the systolic PAP, the decrease by 17 % in SV, 20 % in SI and 25 % in LVEF were revealed in the Killip 2 group comparing with the Killip 1 group. The decrease in LA size by 8 %, LVMI by 16 %, MVE by 18 %, E/A by 46 %, the increase in LVEF by 10 % and IVRT by 11 % comparing with the Killip 3 group were observed. The increase in the size of LA by 11 %, ESD by 20 %, LVMI by 24 %, MVE by 24 %, E/A by 45 % and the systolic PAP by 39 %, and the decrease in SV by 18 %, LVEF by 32 % were detected in the Killip 3 group comparing with the Killip 1 group. The increase in EDD by 9 %, ESD by 6 %, systolic PAP by 18 % and the decrease in LVEF by 17 % were defined in patients with stress HG comparing with the patients with normal glycaemia. The group with stress HG showed the increase in EDD by 10 %, ESD by 5 % and the decrease in LVEF by 15 % comparing with the group with normal glycemia. There were the increase in the size of LA by 12 % and the decrease of LVEF by 20 % in the group with the first identified diabetes comparing with the patients with normal glycaemia. There was an increase in the size of LA by 10 %, IVS by 13 % comparing with the stress HG group; IVS by 13 % comparing with the group with IGT. The group of type 2 diabetes demonstrated the increase in the size of LA by 8 %, ESD by 15 %, and the systolic PAP by 29 %, and the decrease in LVEF by 19 % comparing with patients with normal glycaemia; the increase in the size of LA by 5 % comparing with the stress HG group. There was a significant positive relationship between the level of HG on admission and the size of LA (r = +0.23), ESD (r = +0.27), LVMI (r = +0.25) and a negative relationship with the LVEF (r = -0.23), P < 0.05. A significant positive correlation between the standard deviation of the GP and the size of the LA (r = +0.27), EDD (r = +0.20), ESD (r = +0.23), LVMI (r = +0.32) and a negative relationship with LVEF (r = -0.20), P < 0.05 were determined. A significant positive correlation between the coefficient of variation of the GP and the size of the LA (r = +0.24), the EDD (r = +0.25), the ESD (r = +0.24), LVMI (r = + 0.36) and negative correlation with LVEF (r = -0.22), P < 0.05 were found. The eccentric hypertrophy of the left ventricle developed significantly more often in the group with stress HG and type 2 diabetes in history, comparing with the group with normal glycemia. Conclusions. The increasing of the average blood glucose level, standard deviation and coefficient of GP variation, LA size, ESD, LVMI, and systolic PAP and the decreasing of SI and LVEF were observed in patients with acute Q myocardial infarction and hyperglycemia on admission with the elevation of AHF grade. The study revealed the increase in MVE, E / A ratios and a decrease in IVRT in the Killip 3 group, which indicates the predominance of type 2 diastolic dysfunction comparing with Killip 1 and Killip 2. The patients with hyperglycemia on admission, systolic dysfunction of the left ventricle and pulmonary hypertension, and the patients with stress hyperglycemia and type 2 diabetes in the history demonstrate the eccentric hypertrophy significantly more often than patients with normal glycemia. The Q-MI cardiac remodeling is influenced by the increasing level of glycemia, standard deviation and coefficient of variation of GP on the background of AHF, which is manifested in LVEF decreasing and the increasing of the heart chambers size and left ventricular myocardial mass.